GPA Peptide Attenuates Sepsis-Induced Acute Lung Injury in Mice via Inhibiting Oxidative Stress and Pyroptosis of Alveolar Macrophage. (28th December 2021) - Liu, Yukun; Zhang, Yongsheng; Feng, Quanrui; Liu, Qinxin; Xie, Jie; Li, Hui; Yang, Fan; Liu, Xinghua; Gao, Wei; Bai, Xiangjun; Li, Zhanfei; Wang, Yuchang
Abstract : Acute lung injury (ALI) has been known to be a devastating form of respiratory infection and an important contributor to mortality in intensive care, due to its lacking of effective treatment. Inflammation, oxidative stress, and pyroptosis are associated with multiple kinds of inflammatory diseases such as ALI. It is commonly accepted that Gly-Pro-Ala (GPA) peptide regulates oxidative stress and pyroptosis in different kinds of inflammatory diseases. Our study is aimed at exploring the regulatory function and protective effects of GPA peptides on ALI. In the current study, the cecal ligation and puncture (CLP) technique was used to evoke sepsis in mice, and GPA peptide was administered intraperitoneally with different concentrations (50, 100, and 150 mg/kg) after CLP. Histopathological changes and the ratio of wet-to-dry in lung were recorded and analyzed. We also investigated the level of oxidative stress, inflammation, and pyroptosis. Results showed that GPA peptide significantly ameliorated CLP-stimulated lung tissue injury, impeded proinflammatory cytokine release, and reduced inflammatory cell infiltration. Additionally, GPA peptide suppressed oxidative stress and caspase-1-dependent pyroptosis in alveolar macrophages. Furthermore, our study showed that the GPA peptide prevents alveolar macrophage from undergoing pyroptosis by attenuating ROS. In conclusion, results demonstrated that GPA peptide has protective effects in CLP-stimulated ALI by inhibiting oxidative stress as well as pyroptosis of alveolar macrophage.